Is activation of the intra-S checkpoint in human fibroblasts an important factor in protection against UV-induced mutagenesis? - Sproul, Christopher D (Landes Bioscience, 2013)
The ATR/CHK1-dependent intra-S checkpoint inhibits replicon initiation and replication fork progression in response to DNA damage caused by UV (UV) radiation. It has been proposed that this signaling cascade protects against UV-induced mutations by reducing the probability that damaged DNA will be replicated before it can be repaired. Normal human fibroblasts (NHF) were depleted of ATR or CHK1, or treated with the CHK1 kinase inhibitor TCS2312, and the UV-induced mutation frequency at the HPRT locus was measured. Despite clear evidence of S-phase checkpoint abrogation, neither ATR/CHK1 depletion nor CHK1 inhibition caused an increase in the UV-induced HPRT mutation frequency. These results question the premise that the UV-induced intra-S checkpoint plays a prominent role in protecting against UV-induced mutagenesis.